The French Use of Esparto Grass as Fuel for the Algiers Power Station during World War II (1939–1943) - Chelali , Diffallah (Journal of Ecohumanism, 2025)
Between 1939 and 1943, during the Second World War, colonial authorities in Algeria intensified the exploitation of the region’s natural resources as part of the broader mobilization for the French war effort. French concessionary companies were compelled to declare the materials they extracted so that their allocation and usage could be directed in service of wartime industry. Among the most exploited resources was alfa grass (Stipa tenacissima), a plant that grew abundantly in the hilly and forested regions of Algeria. With the expansion of the railway network, the exploitation of alfa grass increased significantly, particularly by companies involved in paper manufacturing, textiles, and export industries. These firms utilized the plant both as a raw material for the French paper industry and as a substitute fuel for fixed engines at the Algiers power station, especially amid shortages of coal. This intensive exploitation, driven by the needs of the colonial economy, marked the beginning of an environmental and economic depletion that served French industrial interests at the expense of local resources.